SOME ORGANIC CONSTITUENTS OF FINS OF THE CAT-FISH, WALLAGO ATTU (BL. AND SHN.) - Saraswat, R C; Ram, Newton (Indian Journal of Fisheries, 2011)
Crude fat, total nitrogen and crude protein of whole fins of the cat-fish Wallago attu have been studied with reference to different growth stages. All the three constituents increase at the growth stage II, while they decrease at the stage III. At stages I and II thirteen amino acids and at stage III sixteen amino acids of the collagen group are present. At stages I and III glycine and glutamic acid are in traces. Though the variations are marked they are not regular.